Implementation of Community-Based Islamic Religious Education in Binjai City - Vira Regina Cahyani; Afrahul Fadhila Daulai; Humaidah Br. Hasibuan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research, entitled